The evolving landscape: magnetic resonance imaging in active surveillance for prostate cancer management - De la Parra, Irene; Gómez Rivas, Juan; Gutiérrez, Beatriz; Marugán, María Jesús; Enikeev, Dmitry; Somani, Bhaskar K.; Barrera, Jerónimo; Moreno-Sierra, Jesús (Frontiers in Urology, 2024)
Since overdiagnosis and overtreatment pose significant risks in managing prostate cancer (PCa), active surveillance (AS) is the most common treatment in low-risk patients. However, there is no general agreement yet on the inclusion criteria and the required follow-up. Multiparametric magnetic resonance imaging (mpMRI) of the prostate was born as a useful device in these patients both in diagnosis and follow-up, and it is widely used in daily clinical practice. We reflect on the most current evidence described in the literature on the topic, its results, and our experience.